A United Nations Renaissance What the UN is, and what it could be - Trent, John E.; Schnurr, Laura (Verlag Barbara Budrich, 2017)
This short introduction to the United Nations analyzes the organization as it is today, and how it can be transformed to respond to its critics. Combining essential information about its history and workings with practical proposals of how it can be strengthened, Trent and Schnurr examine what needs to be done, and also how we can actually move toward the required reforms. This book is written for a new generation of change-makers ó a generation seeking better institutions that reflect the realities of the 21st century and that can act collectively in the interest of all.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Political Science / Intergovernmental Organizations; Political science; Electronic books